Cutaneous Manifestations of Angioimmunoblastic T-Cell Lymphoma: Clinical and Pathological Characteristics. (April 2015) - Botros, Noha; Cerroni, Lorenzo; Shawwa, Allam; Green, Peter J.; Greer, Wenda; Pasternak, Sylvia; Walsh, Noreen M.
Abstract : Abstract: Angioimmunoblastic T-cell lymphoma (AITL), an uncommon variant of peripheral T-cell lymphoma, affects the skin in approximately 50% of cases. Its protean clinical and histopathological cutaneous manifestations pose a challenge in diagnosis, particularly when these precede the diagnosis of AITL on a lymph node biopsy. In this retrospective study, we compared 11 cases of AITL with cutaneous manifestations (mean age 67 years; male:female ratio 1:0.8; 24 skin biopsies) with 20 control cases of inflammatory and non-AITL lymphomatous diseases (mean age 52 years; male:female ratio 1:1.5; 26 skin biopsies). Clinical, histopathological, immunohistochemical, and molecular data were documented. New insights into the clinical evolution of cutaneous involvement by AITL (C-AITL), from early macular, through papular to nodular stages, were observed. Microscopically, a parallel increment in the density of the dermal infiltrate and in the detection of lymphocyte cytological atypia was noted over time. Identification and quantification of follicular T-helper cells (Tfh), the neoplastic lineage, by immunohistochemistry helped to separate cases of C-AITL from inflammatory controls, offering promise as a useful diagnostic adjunct. The presence of T-cell clonality did not have discriminatory value between the 2 groups. Our work suggests that the early maculopapular phase of C-AITL eludes identification on pathological grounds alone and that features such as cytological atypia and high endothelial venules lack diagnostic specificity. In the context of (1) a rash that simulates a drug/viral exanthem or an acute manifestation of a connective tissue disorder, but proves recalcitrant, (2) constitutional abnormalities and/or lymphadenopathy that persist, and (3) a Tfh cell-rich perivascular dermatitis, the diagnosis of early C-AITL can be suspected, but not confirmed, without the benefit of a lymph node biopsy. The later nodular phase of C-AITL occurring in a similar constitutional background, can usually be discerned as lymphomatous, clinically and pathologically. Here a Tfh cell-rich infiltrate is a clue to the specific diagnosis, but confirmation by a nodal evaluation remains mandatory. Despite the difficulty in establishing a diagnosis of C-AITL in its early stages, and speculation that the initial eruptions might be reactive in nature, our sequential data support the concept that these are lymphomatous ab initio. To address the diagnostic challenge presented by this disease, meaningful integration of clinical and pathological data is imperative.